Ghrelin Cells in the Gastrointestinal Tract. (28th February 2010) - Sakata, Ichiro; Sakai, Takafumi
Abstract : Ghrelin is 28-amino-acid peptide that was discovered from the rat and human stomach in 1999. Since the discovery of ghrelin, various functions of ghrelin, including growth hormone release, feeding behavior, glucose metabolism, memory, and also antidepressant effects, have been studied. It has also been reported that ghrelin in the gastrointestinal tract has an important physiological effect on gastric acid secretion and gastrointestinal motility. Ghrelin has a unique structure that is modified byO -acylation with n-octanoic acid at third serine residues, and this modification enzyme has recently been identified and named ghrelinO -acyl transferase (GOAT). Ghrelin is considered to be a gut-brain peptide and is abundantly produced from endocrine cells in the gastrointestinal mucosa. In the gastrointestinal tract, ghrelin cells are most abundant in the stomach and are localized in gastric mucosal layers. Ghrelin cells are also widely distributed throughout the gastrointestinal tract. In addition, abundance of ghrelin cells in the gastric mucosa is evolutionally conserved from mammals to lower vertebrates, indicating that gastric ghrelin plays important roles for fundamental physiological functions. Ghrelin cells in the gastrointestinal tract are a major source of circulating plasma ghrelin, and thus understanding the physiology of these cells would reveal the biological significance of ghrelin.